(untitled) (Damascus University Journal of Historical Studies, 2026)
It is often said that the glory of the Sassanian Empire was built on the strength of its formidable armies and the bold campaigns of its valiant kings. This is an undeniable truth, as the Sassanian military, with its diverse units and formations, served as the powerful arm of the kings, achieving their expansionist goals. The research includes an introduction to the Sassanian state, the conditions in Iran before the Sassanian era, and the military heritage of the preceding states. It explores the various strategies employed by Sassanian leaders and military commanders in their campaigns and battles. These strategies included gathering intelligence on the enemy, utilizing special units dedicated to deception and misinformation, and employing various ruses and stratagems, such as distracting the enemy, using camouflage and deception, and luring the enemy into traps. These deceptive tactics had a significant impact on undermining the capabilities of powerful armies, such as those of the Byzantine Empire. Without these strategies, it would have been difficult for the Sassanians to overcome such formidable foes, highlighting the crucial role of military deception in warfare. The ability to devise and execute effective military ruses often determines who can achieve victory with minimal resources. The research concludes that the success of the Sassanids in their battles was not merely a coincidence but rather the result of meticulous strategic planning and intelligent use of deception, compensating for any numerical or equipment disadvantages they faced.